The Rockefeller Team Science Leadership training program: Curriculum, standardized assessment of competencies, and impact of returning assessments. Issue 1 (13th August 2021) - Vaughan, Roger; Romanick, Michelle; Brassil, Donna; Kost, Rhonda; Neville-Williams, Maija; Gottesman, Riva; Devine, Rita; Manukonda, Prasanth; Ronning, Andrea; O'Sullivan, Barbara; Capili, Bernadette; Macarthur, Robert; et al.
Abstract: The ability to effectively lead an interdisciplinary translational team is a crucial component of team science success. Most KL2 Clinical Scholars have been members of scientific teams, but few have been team science leaders. There is a dearth of literature and outcome measures of effective Team Science Leadership in clinical and translational research. We focused our curriculum to emphasize Team Science Leadership, developed a list of Team Science Leadership competencies for translational investigators using a modified Delphi method, and incorporated the competencies into a quantitative evaluation survey. The survey is completed on entry and annually thereafter by the Scholar; the Scholar's primary mentor and senior staff who educate and interact with the Scholar rate the Scholar at the end of each year. The program leaders and mentor review the results with each Scholar. The survey scales had high internal consistency and good factor structure. Overall ratings by mentors and senior staff were generally high, but ratings by Scholars tended to be lower, offering opportunities for discussion and career planning. Scholars rated the process favorably. A Team Science Leadership curriculum and periodic survey of attained competencies can inform individual career development and guide team science curriculum development.